The use of weightlifting pulling movements in sport (continued) - Common pulling errors - Stone, M.; Gattone, M.; Stone, M.; Schilling, B.; Pierce, K.; Byrd, R.
Content: - Common errors in the pull - Results of starting the pull too early - Correction of a common error - Pulling back - Jumping back